Spray-Dried Cytisine-Loaded Matrices: Development of Transbuccal Sustained-Release Tablets as a Promising Tool in Smoking Cessation Therapy - Giuseppe Angellotti; Giulia Di Prima; Amalia Giulia Scarpaci; Fabio D’Agostino; Giuseppina Campisi; Viviana De Caro (Pharmaceutics, 2022)
Cytisine (CYT) has emerged as a promising molecule to treat nicotine addiction, since it acts as a partial agonist of nicotinic acetylcholine receptors. However, its unfavorable pharmacokinetic properties lead to multiple administrations per day, reducing the patient’s compliance and increasing the side effects. To overcome these drawbacks, CYT buccal administration is here proposed. Firstly, CYT stability in the buccal environment was assessed and its intrinsic ability to permeate/penetrate the tissue was determined by applying CYT solutions at increasing concentrations. Furthermore, a spray-drying method was selected and optimized as it is an eco-friendly, easily scalable and effective technique to obtain uniform and reproducible CYT-loaded (5% w/w) pharmaceutical powders, which were directly compressed, thus obtaining different buccal delivery systems (BDSs). The obtained BDSs were homogeneous and reproducible and embedded CYT in its amorphous form. The mechanism of CYT release was evaluated in vitro and found to be mainly driven by a Fickian diffusion phenomenon. Predominantly, the ex vivo permeation assays highlighted the ability of the BDSs to enhance CYT permeation, also producing high drug fluxes through the mucosa. Speculative mathematical evaluations based on the already-known CYT pharmacokinetic parameters showed that CYT-loaded BDSs could potentially be sufficient to obtain a therapeutic effect, thus making the reported formulations suitable candidates for further in vivo trials.